PENGARUH MUTASI TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - SHINTA RUNDENGAN; RIANE JOHNLY PIO; MAX PANGKEY (JURNAL ADMINISTRASI BISNIS, 2014)
The most important resource in an organization is human resource. Human resources isthe most important factor for the effectiveness of the organization, because of their behavior in the longterm will facilitate or hinder the achievement of organizational goals. Those people in the organizationprovide power, talent, creativity and effort to the organization. Mutations are changes positions, places,work both horizontally and vertically (promotion or demotion) in an organization.Mutation is the one tool that is used to determine whether it can improve work performance ornot in order to achieve the desired level of success of the organization. Job performance is the result of thequality and quantity of work achieved by an employee or employees in carrying out their duties inaccordance woth the responsibilities assigned to him. The study aims to determine whether there is anyeffect of the mutation on the performance of employees.The data obtained in this study is through observation, interviews, and dissemination kuisioner to45 officers with an overview of the respondents are included characteristics consisting of age, gender,length of service and education last. In this study using simple correlation analysis approach and a simplelinear regression.From the research conducted, found no effect of the mutation on work performance. Thereforeagencies or organizations should pay attention to things that include the performance of a mutation that,employee may continue to develop for the betterment of the organization on for the betterment of theorganization or for employees.Keywords : Mutation , Work Performance